THE FORMATION OF THE INFORMATIA INFOSTRUCTURE OF IN UKRAINE AS ONE OF THE COMPONENTS OF NATIONAL SECURITY - Полисаєв, О. П.; Шедяков, В. Є. (Proceedings of the National Aviation University Series Philosophy Cultural, 2021)
The paper deals with the problem of National infrastructure under the condition of Ukrainian state development. The stable trends of the mentioned process when there exists the threat to the national security of the country, and possible ways of its minimization have been analysed. Specific functioning of the. Information system of Ukraine under globalization and social in Ukraine system of citizenship formation has been shown.